Pengobatan pada Sistem Panca Indra - Liss Dyah Dewi Arini; Bagus Muhamad Ridwan; Hussein Omar Savero; Ilham Ary Pangestu; Nizar Athallah (Institut Nalanda, 2024)
The human five sensory system, consisting of sight, hearing, smell, taste and touch, is an important part of everyday life. Disturbances in any one of the senses can significantly interfere with a person's quality of life. Therefore, effective treatment is needed to maintain the health and quality of function of the five sensory systems. Treatment of the sensory system involves a variety of approaches, depending on the type of disorder experienced. The use of medications, physical therapy, speech therapy, and surgical interventions are some of the commonly used methods.